The Implementation of Technology-Based Learning Models in Early Childhood Education Curriculum - Mardan, Micha; Husna, Lailatul; Cindia, Cindia (The Future of Education Journal, 2024)
This research aims to analyze the implementation of technology-based learning models in the early childhood education curriculum at PAUD IT Yadiaksa Sungai Rumbai. Along with the rapid development of technology, the integration of technology in early childhood learning is one of the innovations that is expected to improve the quality of learning. The research method used is qualitative with a case study approach. Research subjects included teachers, students and parents at PAUD IT Yadiaksa . Data was collected through direct observation in class, in-depth interviews with teachers and parents, as well as documentation of learning materials. The research results show that the use of technology, such as educational applications and multimedia devices, has a positive impact on children's involvement in the learning process. Children are more enthusiastic and interactive when technology is used as a learning aid. However, challenges faced include limited access to technology in some families and the need for intensive assistance by teachers and parents to ensure technology is used effectively. Overall, the technology-based learning model at PAUD IT Yadiaksa shows great potential in supporting children's development, noting that there must be a balance between the use of technology and direct interaction that supports children's social and emotional aspects.